Crime in the art and antiquities world illegal trafficking in cultural property - Manacorda, Stefano; Chappell, Duncan (Springer New York, 2011)
The theft, trafficking, and falsification of cultural property and cultural heritage objects are crimes of a particularly complex nature, which often have international ramifications and significant economic consequences. Organized criminal groups of various types and origins are involved in these illegal acts. The book Crime in the Art and Antiquities World has contributions both from researchers specializing in the illegal trafficking of art, and representatives of international institutions involved with prevention and detection of cultural property-related crimes, such as Interpol and UNESCO. This innovative volume also includes an Appendix of the existing legal texts, i.e. international treaties, conventions, and resolutions, which have not previously been available in a single volume. This work is a unique and useful reference for scholars and private and public bodies alike.